Total synthesis and determination of relative and absolute configuration of multiplolide A - Ramana, C. V.; Khaladkar, Tushar P.; Chatterjee, Soumitra; Gurjar, Mukund K. (Journal of Organic Chemistry, 2008)
A flexible approach for total syntheses of possible multiplolide A diastereomers establishing the relative and absolute configuration is documented. The adopted strategy features ring-closing metathesis (RCM) as the key reaction and screening of a set of substrates for the feasibility of RCM in general and for the requisite E-configuration of ring olefin in particular. Selective protecting groups manipulation prior to the assembly of the central macrocyclic core was instrumental in installing the epoxide functionality on a fully deprotected nonenolide at the end of the synthesis.

Click synthesis of isomeric compounds for assessing the efficiency of the bifurcated Br center dot center dot center dot NO2 synthon - Ramana, C. V.; Chatterjee, Soumitra; Durugkar, Kulbhushan A.; Gonnade, Rajesh G. (Crystengcomm, 2009)
We report herein the extention of the azide-alkyne ``click reaction'' to crystal engineering and synthesize a collection of isomeric compounds with modular positioning of Br and NO2 on a tricyclic template and crystal structural analyses of the derived isomers. It is quite remarkable to notice that none of the isomers displayed the bifurcated three-center NO2 center dot center dot center dot Br supramolecular synthon in their crystal structures

Evaluation of viability of halogen•••O2N interactions: insight form crystal packing in a series of isomeric halo and nitro substituted triaryl compounds with modular positioning of halogen and NO2 groups - Ramana, Chepuri V.; Goriya, Yogesh; Durugkar, Kulbhushan A.; Chatterjee, Soumitra; Krishnaswamy, Shobhana; Gonnade, Rajesh G. (CrystEngComm, 2013)
A series of isomeric triaryl compounds with a modular positioning of the halogen and NO2 groups have been synthesized by the azide–alkyne “click reaction” and have been characterized by single crystal X-ray structure analysis. This isomeric series has provided an opportunity for understanding the efficiency of the bifurcated halogen⋯NO2 synthon in the organization of the molecules in the crystalline lattice. The changes in molecular conformation, crystal packing and supramolecular aggregation due to the change in the relative positioning of the complementary groups, halogen atom and the NO2 group on ring A and ring C respectively, have been discussed. All the isomers synthesized are crystalline and establish the triazole as a reliable linker for crystal engineering oriented molecular synthesis. The 2-NO2 derivatives display in general, a helical architecture and 3-NO2 derivatives exhibit a centrosymmetric dimeric assembly via the complementary C–H⋯O interactions leading to either a helical or a 2-dimensional sheet pattern. The molecular organization in 4-NO2 derivatives revealed in general a 2D sheet pattern.